2008
DOI: 10.1002/ceat.200800198
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and Holdup in Multiphase Packed Bed Microreactors

Abstract: Liquid holdup and dispersion are reported for a column of 2 mm internal diameter, filled with 0.1 mm spherical particles, for multiphase flows with hydrocarbon liquid flow rates of 10-100 lL/min and nitrogen gas flow rates of 50-1000 lL/min using different tracers with varying diffusion coefficients and vapor pressures. It was found that the liquid holdup (liquid volume/external void volume) was between 0.65 and 0.85, with variations between different experiments and limited impact of flow rate on the holdup. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 24 publications
1
39
0
1
Order By: Relevance
“…Bellos et al (2004) showed the first two cases: (1) the mean residence time and variance are the same for both tracers, (2) the mean residence time is the same but the variance is larger for the volatile tracer. Marquez et al (2008) reported the last case: (4) the mean residence time is shorter for the volatile tracer but the variance is the same as the one for a non-volatile tracer. We try to identify the relative rate of mass transfer versus flow for the four different cases performing RTD simulations over a wide range of Stanton values.…”
Section: Simultaneous Liquid and Gas Rtd Curves For A Volatile Tracermentioning
confidence: 87%
See 4 more Smart Citations
“…Bellos et al (2004) showed the first two cases: (1) the mean residence time and variance are the same for both tracers, (2) the mean residence time is the same but the variance is larger for the volatile tracer. Marquez et al (2008) reported the last case: (4) the mean residence time is shorter for the volatile tracer but the variance is the same as the one for a non-volatile tracer. We try to identify the relative rate of mass transfer versus flow for the four different cases performing RTD simulations over a wide range of Stanton values.…”
Section: Simultaneous Liquid and Gas Rtd Curves For A Volatile Tracermentioning
confidence: 87%
“…In previous work, we reported shorter residence times for the volatile compounds in a multi-phase micro-packed bed (Marquez et al, 2008). In this work, we present our modeling results for isothermal conditions and zero pressure drop, just to limit the parameter space.…”
Section: Article In Pressmentioning
confidence: 95%
See 3 more Smart Citations